Reverse taxonomy applied to the Brachionus calyciflorus cryptic species complex: Morphometric analysis confirms species delimitations revealed by molecular phylogenetic analysis and allows the (re)description of four species - Michaloudi, Evangelia; Papakostas, Spiros; Stamou, Georgia; Neděla, Vilém; Tihlaříková, Eva; Zhang, Wei; Declerck, Steven A J (PloS one, 2018)
The discovery and exploration of cryptic species have been profoundly expedited thanks to developments in molecular biology and phylogenetics. In this study, we apply a reverse taxonomy approach to the Brachionus calyciflorus species complex, a commonly studied freshwater monogonont rotifer. By combining phylogenetic, morphometric and morphological analyses, we confirm the existence of four cryptic species that have been recently suggested by a molecular study. Based on these results and according to an exhaustive review of the taxonomic literature, we name each of these four species and provide their taxonomic description alongside a diagnostic key.
Keywords: DNA helmintů; druhová specificita; vířníci; DNA, Helminth; Ecosystem; fylogeneze; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; sladká voda; Fresh Water; Species Specificity; Netherlands; Rotifera; Nizozemsko; Animals; ženské pohlaví; Microscopy, Electron, Scanning; zvířata; ekosystém; Female; mikroskopie elektronová rastrovací; Molecular Biology; molekulární biologie